Estudo de prevalência dos casos de meningite no Hospital Universitário João de Barros Barreto - COSTA, Débora Lobato de Souza (2019)
Meningitis is an inflammation of the meninges, the protective membranes covering the brain and spinal cord. Transmission is from person to person through respiratory tract or by direct contact with secretions of the patient. Meningitis is a group of diseases whose notification is compulsory. This study aims to determine the prevalence of patients with meningitis admitted to the University Hospital João de Barros Barreto in accordance with the following variables: age, sex, origin, clinical manifestations, type of meningitis, co infections and type of discharge, from January 2007 to December 2010. This is a quantitative, descriptive, retrospective and transversal. The data source used was the Information System of Notifiable Diseases Surveillance Center. Within 4 years, were registered from the database 915 cases diagnosed with meningitis. Noteworthy was the age group 1-12 years with 327 cases during the study period corresponded to 35.74%. The number of cases of male patients was higher than the number of female cases. The meso Metropolitan Belém showed the largest number of cases representing 59.13% of cases, followed by meso Northeast of Pará with 30.60% of cases. The most common clinical manifestations were fever (98.57%), headache (87.54%), vomiting (86.12%) and neck stiffness (71.47%). The bacterial meningitis presented himself as a major cause of the number of admissions during the study period, accounting for 48.42% of admissions. Aids was the most frequent co infection. Given the scarcity of studies regarding this condition in this region, there is great significance in the data collected since the monitoring of meningitis is useful to adopt control measures for prevention, diagnosis as well as fast and early treatment. So in any scenario, be it local, regional or international, there is a real and urgent need to join efforts in fighting meningitis.